The The Sandwich Technique For Minimally Invasive Repair Of Pectus Carinatum - Diaz, Yara Lopes (2024)
Introduction: Minimally invasive repair of pectus carinatum (MIRPC) has been performed using the Abramson technique in which the bar that compresses the sternum is fixed with steel wires on the ribs. A 14-year-old patient underwent to a MIRPC using a sandwich technique in which two metallic bars fixed with bridges were implanted below the sternum under thoracoscopic vision, and another bar in a subcutaneous tunnel was implanted above. This technique has the potential to avoid specific problems related to the original technique like loosening of support for correction (broken wire), avoidance of induction of pectus excavatum or subcutaneous tissue adhesion.